Relationship Between Self-Concept And Self-Cofidence In Young Women At SMPN 1 Manisrenggo - Puji Rahayu, Prastiwi (Sahabat Publikasi Kuu, 2024)
Background: In the development of adolescents, the most important thing to do is to form a self-identity that is obtained from an individual’s understanding of the self-concept they have. Self-concept is the most important thing in the lives of adolescents because self-concept can determine how individuals behave. Individuals with a good self-concept tend to be more optimistic, always have a positive attitude towards everything, and show self-confidence. Confidence is an important factor in determining individual success. Objective: This study aims to determine the relationship between self-concept and self-confidence in young women. Method: This research is a quantitave study with a cross sectional approach. The data collection technique used was purposive sampling with a total of 98 respondents. The instruments used were demographic data questionnaires, self-concept questionnaires and self-confidence questionnaires. The relationship between the two variables was analyzed by kendall tau correlation test. Result: The result showed that there was a relationship in a positive direction between self-concept and self-confidence in young women at SMPN 1 Manisrenggo with p-value of 0,0017. Counclusion: It is hoped that with this research young women can maintain self-confidence, so that young women can find out what has been achieved, set goals, and always think positive. Keywords: Self-Concept, Self-Confidence, Teenage Gril